Organic matter transfer in Lake Superior's food web: Insights from bulk and molecular stable isotope and radiocarbon analyses. (5th October 2015) - Kruger, B. R.; Werne, J. P.; Branstrator, D. K.; Hrabik, T. R.; Chikaraishi, Y.; Ohkouchi, N.; Minor, E. C.
Abstract: A suite of isotopic methods were combined to provide a comprehensive investigation of organic matter transfer and consumer‐resource links in a large lake food web. We applied compound specific isotope analysis (CSIA) of nitrogen within amino acids of organisms, a relatively new method and one not yet widely applied to large lake systems, to determine the trophic positions of several dominant species. Comparison of this CSIA trophic designation to those calculated by traditional bulk stable carbon and nitrogen isotope ratios, as well as gut content analyses, revealed this CSIA method to be the most representative of known trophic links in Lake Superior. Limnocalanus macrurus, an omnivorous copepod, was found to occupy a trophic position higher than would have been predicted based on gut analyses, and one full trophic position above primary consumer Daphnia . Radiocarbon analysis of bulk zooplankton and fish tissue was employed as a modern carbon tracer to elucidate the relative ages of carbon incorporated into, and propagated through, the food web. Comparison of animal tissue, non‐living carbon pools (DOC, DIC), and POC radiocarbon content indicate the food web is supported predominately by newly synthesized autochthonous material. The uniquely depleted radiocarbon signature of the benthic amphipod Diporeia, attributed to consumption of aged sedimentary or allochthonous material, was not reflected in its known predators, indicating little overall incorporation of that aged carbon source into the pelagic food web. This multi‐method isotopic investigation extends our understanding of food web structure and organic matter flow in this large lake.